Beiträge zur Collembolenfauna der Höhlen deutscher Mittelgebirge Teil II (mit Anhang über einige Dipluren). - Palissa, Alfred (Contributions to Entomology = Beiträge zur Entomologie, 2000)
The Collembola of 102 caves in the German mountain ranges Harz, Kyffhäuser, Thüringer Wald and Zittauer Gebirge were investigated during the period 1988-1991. Most of the Collembola were collected with pitfall traps filled with ethylene glycol. Depending on the size of the caves, 1-20 traps per cave were used. - More then 30000 specimens of 82 species were captured. Some additional species are still unidentified. Arrhopalites troglophilus sp. n. is described. The zoogeographic and taxonomic characteristics of the recorded species are reviewed and critical species are discussed. - For the Schaefferia species, the distribution in the four mountain ranges is updated. - Tetrodontophora bielanensis is for the first time recorded from the Kyffhäuser, far north of the previously known range of the species. Keywords Collembola, Diplura, Faunistics, Taxonomy, German highlands. Nomenclatural Acts troglophilus Palissa, 2000 (Arrhopalites), spec. n.